Exit-Knowledge of Ambulatory Patients About Medications Dispensed in Government Hospital in Eastern Ethiopia: The Need for Focused Patient Counseling - Nigatu Hirko; Dumessa Edessa; Mekonnen Sisay (Frontiers Media S.A., 2018)
Background: In the counseling process, a multi-cultural competence of dispenser is among the key factors affecting his/her successful communication with patients for achieving optimal use of medications. For patients to use dispensed drugs appropriately, it is a must for them to understand the medication related information provided by the dispenser. Hence, the objective of this study was to identify parameters that likely affect ambulatory patients' knowledge of medication(s) provided at the exit of outpatient pharmacy of Federal Harar Police Hospital, Eastern Ethiopia.Methods: Cross-sectional study design was employed to conduct this study. An interview of patients was made at the exit of hospital pharmacy using a semi-structured questionnaire. The interview tool primarily assessed the knowledge of the patients for a maximum of three medications provided. Statistical Package for Social Sciences (SPSS), Version 20.0, was employed for analysis of the data. Chi-squared test was done to retain parameters with potential to have association; and the retained parameters were adjusted by performing bivariate and multivariate logistic regression analyses.Results: The result showed that only 37.2, 33.4 and 28.7% of the patients were able to recall the name of the drug(s), common side effects, and actions to be taken for missed doses, respectively. The likelihood of patients' knowledge for dispensed medications was high among patients aged 19-39 years (adjusted odds ratio [AOR]: 5.0; 95% CI: 1.04-24.2) and who thought their communication with dispenser had been polite (AOR: 4.62; 95% CI: 1.48-14.4). However, the knowledge status was found low among patients who were Afan Oromo speakers (AOR: 0.58; 95% CI: 0.35-0.95) and who came from rural residence (AOR: 0.48; 95% CI: 0.25-0.90).Conclusion: A high proportion of patients were unable to recall the drug (s) name, associated common toxicities, and actions to be taken in case of missed dose. In addition, patients who were at early adulthood and who were positive for the politeness of dispenser had better exit-knowledge of their medication. Therefore, for the patients' clear understanding of medications provided, it is mandatory to optimize patient-dispenser communication possibly by adapting multi-cultural communication skills and by providing focused training for dispensers to address factors that likely affect patient-dispenser interactions.